Rectally Administered Low-Dose Diclofenac Has No Effect on Preventing Post–Endoscopic Retrograde Cholangiopancreatography Pancreatitis: A Propensity Score Analysis. Issue 7 (11th August 2021) - Takaori, Ayaka; Ikeura, Tsukasa; Hori, Yuichi; Ito, Takashi; Nakamaru, Koh; Masuda, Masataka; Mitsuyama, Toshiyuki; Miyoshi, Hideaki; Shimatani, Masaaki; Takaoka, Makoto; Okazaki, Kazuichi; Naganuma, Makoto
Abstract : Objectives: We evaluated the preventive effect of low-dose diclofenac (25–50 mg) on post–endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP) by propensity score matching analysis. Methods: We retrospectively analyzed the data of 515 patients who underwent ERCP for the first time with or without the rectal administration of low-dose diclofenac before the procedure. For the purpose of minimization of the intrinsic selection bias, we compared the incidence rate of PEP between the diclofenac and control group after propensity score matching. Results: Post-ERCP pancreatitis developed in 15 patients (2.9%). There was no significant difference in the incidence of PEP between the diclofenac (2.4%) and control group (3.3%) ( P = 0.608). One hundred ninety matched pairs were generated by propensity score matching and analyzed; however, the incidence rate of PEP was the same in both groups (2.1%, P = 1.000). In the subgroup analysis using data of patients with high-risk factors for developing PEP, the incidence rate of PEP was comparable between the diclofenac (3.8%) and control groups (4.0%) ( P = 0.917). Conclusions: In our propensity score analysis, rectal administration of low-dose diclofenac was not shown to be useful in preventing PEP.